Adaptation, psychometric properties and feasibility of the Professionalism Scale Germany = Adaptation, psychometrische Eigenschaften und Anwendbarkeit der Professionalitäts-Skala Deutschland - Roos, Marco; Pfisterer, David; Krug, Doris; Ledig, Thomas; Steinhäuser, Jost; Szecsenyi, Joachim; Goetz, Katja (Zeitschrift für Evidenz, Fortbildung und Qualität im Gesundheitswesen, 2016)
Pre- and postgraduate education is meant to be competency-based. Over the last two decades various competency frameworks have been published. An important aspect of competency is professionalism, being discussed widely in the literature while a clear-cut definition is still lacking. The purpose of this study was to translate the Nijmegen Professionalism Scale into the German language, to adapt the scale to the German setting and to examine the psychometric properties, test-retest reliability and feasibility of the culturally adapted instrument designed to assess professionalism in general practice, in addition to the validity of the concept of professionalism and to testify the transfer across linguistic, cultural and societal differences.
Mit einer Zusammenfassung in englischer und deutscher Sprache
Gesehen am 05.05.2020